(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Cataract is the most common cause of reversible blindness worldwide, which has been associated with various causative risk factors. Hence, we aim to study the factors that might play a role in cataractogenesis. Materials and methods. A total of 240 eyes of 240 subjects were included for the study, which consisted of 120 cases with a cataract and 120 matched controls, and in them various factors like blood pressure, body mass index (BMI), smoking, sun exposure, and serum cholesterol were studied. Results: A statistically significant difference between the two groups. Subjects who were smokers, had a longer exposure to sun, and had higher serum cholesterol level were found to be positively associated with development of cataract. No significant association between BMI and blood pressure was observed. Conclusion: Higher cholesterol levels, increased sun exposure, and smoking habit play a role in the development of cataract, and these are modifiable risk factors. Hence, control of these might help in delaying formation and progression of cataract.